2015
DOI: 10.1002/14651858.cd000032.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal dietary education and supplementation to increase energy and protein intake

Abstract: Antenatal dietary education and supplementation to increase energy and protein intake (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
235
2
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(263 citation statements)
references
References 135 publications
18
235
2
8
Order By: Relevance
“…9 In the meta-analysis of Ota et al, apart from abovementioned advantages, was shown that pregnant women, who got advice on healthy diet principles from healthcare professionals, increased protein consumption. 10 Other studies analyzed not only women's awareness level but also evaluated an impact of medical specialists training.…”
Section: Discussionmentioning
confidence: 99%
“…9 In the meta-analysis of Ota et al, apart from abovementioned advantages, was shown that pregnant women, who got advice on healthy diet principles from healthcare professionals, increased protein consumption. 10 Other studies analyzed not only women's awareness level but also evaluated an impact of medical specialists training.…”
Section: Discussionmentioning
confidence: 99%
“…La suplementación proteicoenergética equilibrada parece mejorar el crecimiento fetal y puede reducir el riesgo de muerte fetal y de recién nacidos pequeños para la edad gestacional. Mientras tanto, la suplementación muy alta de proteínas podría ser dañina para el feto (36) .…”
Section: La Alimentación Durante La Gestaciónunclassified
“…6 İyi kalitede kanıt düzeyinde antenatal takiplerde beslenme danışmanlığı verilmesinin, gebelikte aşırı kilo alımını önleyebileceği belirtilmektedir Ota ve ark (2015) tarafından yapılan 9.030 gebenin katıldığı 17 randomize kontrollü araştırma-nın meta analizinde; ebeler tarafından antenatal dö-nemde verilen beslenme eğitiminin etkileri ince lenmiştir. 18 Antenatal beslenme eğitiminin preterm doğum ve düşük doğum ağırlığı riskinin azalmasında, yenidoğan baş çevresinin artmasında, yetersiz beslenen kadınlarda bebek doğum ağırlığının artmasında ve protein alımının artmasında etkili olduğu görülmüştür. 18 Gebelikte kilo alımı kişinin BKI hesaplanarak dikkate alınmalıdır.…”
unclassified
“…18 Antenatal beslenme eğitiminin preterm doğum ve düşük doğum ağırlığı riskinin azalmasında, yenidoğan baş çevresinin artmasında, yetersiz beslenen kadınlarda bebek doğum ağırlığının artmasında ve protein alımının artmasında etkili olduğu görülmüştür. 18 Gebelikte kilo alımı kişinin BKI hesaplanarak dikkate alınmalıdır. Uluslararası Tıp Enstitüsü'nün sınıflamasına göre; 19 BKI <18.5 kg/m2 -12.5-18 kg, BKI 18.5-24.9 kg/m2-11.5-16 kg BKI 25-29.9 kg/m2-7-11.5 kg, BKI > 30 kg/m2-5-9 kg.…”
unclassified